On the structure of the clause in Proto-Sino-Tibetan and its development in the daughter languages = 试探原始汉藏语的子句结构及其演变 - LaPolla, Randy J. 罗仁地 (2021)
In Sino-Tibetan historical linguistics, much has been done in reconstructing the sound system of Proto-Sino-Tibetan and in reconstructing a large number of cognate lexical items assumed to have been part of Proto-Sino- Tibetan, and there has been considerable work in terms of what morphology can or cannot be reconstructed to Proto-Sino-Tibetan, but it is much harder to say that two syntactic patterns are cognate than to say that two morphological paradigms or particular words are cognate. Within the family we find that modern Sinitic varieties vary from most of the Tibeto-Burman languages in terms of basic clause structure. In this paper we look at information structure in Old Chinese to attempt to find a directionality to the changes found in the long period we think of as Old Chinese, and to look back to the starting point of those changes to see what the clause structure of the precursor of Old Chinese might have been. As it turns out to be more similar to the dominant patterns of Tibeto-Burman languages, it allows us to hypothesize what the patterns were in Proto-Sino-Tibetan. 众所周知，汉语族语言与藏缅语族语言有亲属关系，即都来自原始汉 藏语。已有不少研究试探构拟原始汉藏语的语音系统、形态和词汇， 但句法的性质与词汇、形态的性质不一样，难以构拟，尤其是因为汉 语族的语言和大部分的藏缅语族的语言的句子结构不一样。本文试探 用信息结构来了解古汉语词序变化的方向，追溯变化的起点，认为在 史前时代后来演变为古汉语的语言的词序比较接近大部分藏缅语族语 言的词序，因此我们可以推测原始汉藏语的句子结构。